Ezetimibe inhibits platelet activation and uPAR expression on endothelial cells - Becher, Tobias; Schulze, Torsten; Schmitt, Melanie; Trinkmann, Frederik; El-Battrawy, Ibrahim; Akın, Ibrahim; Kälsch, Thorsten; Borggrefe, Martin; Stach-Jablonski, Ksenija (International journal of cardiology, 2017)
Purpose Lipid lowering therapy constitutes the basis of cardiovascular disease therapy. The purpose of this study was to investigate effects of ezetimibe, a selective inhibitor of intestinal cholesterol absorption, on platelets and endothelial cells in an in vitro endothelial cell model. Methods: After a 24h incubation period with ezetimibe (concentrations 1, 50, 100 and 1000ng/ml), human umbilical vein endothelial cells (HUVEC) were stimulated for 1h with lipopolysaccharide (LPS) and were then incubated in direct contact with activated platelets. Following this, the expression of CD40L and CD62P on platelets, and the expression of ICAM-1, VCAM-1, uPAR, and MT1-MMP on endothelial cells were measured by flow cytometry. Supernatants were analysed by enzyme linked immunosorbent assay for soluble MCP-1, IL-6 and MMP-1. Results: The increased expression of uPAR on endothelial cells by proinflammatory stimulation with LPS and by direct endothelial contact with activated platelets was significantly reduced through pre-incubation with 100ng/ml and 1000ng/ml ezetimibe (p<0.05). Platelets directly incubated with ezetimibe but without endothelial cell contact showed significantly reduced CD62P and CD40L surface expression (p<0.05). Ezetimibe had no significant effects on HUVEC expression of MT1-MMP, ICAM-1 and VCAM-1 and on CD40L expression on platelets in direct contact with endothelial cells. Levels of soluble IL-6 in HUVEC supernatants were significantly lower after pre-incubation with ezetimibe. Conclusion: In this in vitro analysis, ezetimibe directly attenuates platelet activation and has significant endothelial cell mediated effects on selected markers of atherosclerosis.